Removing Products of Thermal Degradation from Edible Oils by Zeolite and by Clinoptilolite - Comparison of Results - Sanja Dobrnjac; Ljubica Vasiljević; Stevan Blagojević; Miladin Gligorić; Zoran Obrenović; Vesna Cvijetinović; Dragan Tošković (Journal of Engineering & Processing Management, 2019)
When edible oils are heated above 150 ℃, they undergo thermo-oxidative changes depending on a variety of factors, such as temperature, heating time, type of oil, etc. These changes cause a series of chemical reactions (hydrolysis, oxidation, polymerization, etc.) resulting in the formation of free fatty acids, an increase in the peroxide number and the acid number, a change of color and a decrease in the iodine number. This study investigates changes of the content of free fatty acids, the acid number, and the peroxide number in edible sunflower oil when heating at the temperature range from 110 ℃ to 190 ℃ for 30 minutes, as well as after the adsorption by a natural and a synthetic adsorbent (clinoptilolite and zeolite 4A). The results of the research show that these adsorbents are effective in removing the products of chemical reactions occurring in thermal degradation, which is particularly evident after the adsorption of oil heated at 190 ℃. Somewhat better results were achieved after the adsorption using clinoptilolite, with a 72 % reduction in the content of free fatty acids, 83 % reduction in the acid number, and 43 % reduction in the peroxide number. After the adsorption by zeolite 4A, the content of free fatty acids was reduced by 65%, the acid number by 76 %, and the peroxide number by 39 %. The results obtained open the possibilities of further research aiming at discovering the adsorbents which would be most suitable for the regeneration of used edible oils, after which they could be applied safely for different purposes.
Keywords: edible oil; free fatty acids; acid number; peroxide number; adsorbent